Romans 4 A Critique of N.T. Wright - Lambrecht, Jan 1926- (2013)
In Romans 4 Paul reinterprets data from Gen. 15 and 17. He no longer respects the original context of these chapters but employs the Genesis material for his own reasoning. It would seem that Rom. 4.1 consists of only one question, while the positive answer to it is implied. In Rom. 4.5 Paul states that the still uncircumcised and, according to vv. 6-8, sinful Abraham is justiﬁed through faith. In this way he has become the father of all believers. These conclusions differ from what N.T. Wright claims in his JSNT article.
Keywords: justiﬁcation; Genesis 15 and 17; Romans 4